Electric power generation : the changing dimensions - Tagare, D. M. (Hoboken, N.J. : Wiley-IEEE Press, 2011)
'This book offers an analytical overview of established electric generation processes, along with the present status & improvements for meeting the strains of reconstruction. These old methods are hydro-electric, thermal & nuclear power production. The book covers climatic constraints; their affects and how they are shaping thermal production. The book also covers the main renewable energy sources, wind and PV cells and the hybrids arising out of these. It covers distributed generation which already has a large presence is now being joined by wind & PV energies. It covers their accommodation in the present system. It introduces energy stores for electricity; when they burst upon the scene in full strength are expected to revolutionize electricity production. In all the subjects covered, there are references to power marketing & how it is shaping production. There will also be a reference chapter on how the power market works'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Electric power production